MY SAY: Lessons from the killing fields - Abd Razak, Dzulkifli (2010)
It was 35 years ago, in April 1975, that the Khmer Rouge (KR) defeated the Lon Nol regime of Cambodia. Just last month, the Khmer Rouge Tribunal released a 143-page report on a demographic survey of the "killing fields" under the Democratic Kampuchea government.